Kode Tuturan dalam Kegiatan Pembelajaran di Sekolah - Tri Handoyo, Teguh; Asropah; Septiana, Ika (Sasando, 2025)
This study aimed to describe the forms of speech code used in learning activities at school. The type of this research was qualitative research. The data consisted of utterances, and the data sources came from speakers in the school environment. The population in this study was the speakers within the environment of SMP Negeri 1 Jatinegara. The samples were teachers, students, and school members. The data collection technique used the observation method. A derivative of the observation method was done through tapping. The form of tapping was the free involvement observation method. The instruments used were observation, note-taking, and recording. The data analysis technique involved data collection, data reduction, and conclusion drawing. The results of the study showed that the form of code-switching included switching from Indonesian to Javanese and from Javanese to Indonesian. Meanwhile, the form of code-mixing involved mixing the codes of Indonesian and Javanese languages. The single-language variation showed a consultative register in Indonesian, while the ngoko and bebasan registers were used in Indonesian.